Campbell Union High School track team - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the Campbell Union High School track team posing in uniform with their coach. From left to right are: Elmer Hoerler, Raymond Hulseman, Al Gross, Fred Heinzen, George Benner, Emil Mrak, and D.H. Cramer (coach).